2021
DOI: 10.1039/d1ee02454j
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale interfacial engineering enables highly stable and efficient perovskite photovoltaics

Abstract: The molecular level interface engineering with a multifunctional ligand 2,5-thiophenedicarboxylic acid suppresses interfacial ion diffusion and inhibits I2 formation, which leads to high operational stability with T80 of 3570 h along with PCE of 23.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 59 publications
2
78
0
Order By: Relevance
“…[31][32][33][34][35] A lack of in-depth understanding of the heterojunction interfaces and appropriate interface designs, specifically the buried interfaces under polycrystalline perovskite films, is impeding further advancements in perovskite photovoltaic performance and stability. [36][37][38][39][40][41][42] To date, many researches mainly focus on the top surfaces of perovskite. [43][44][45][46][47] However, due to the accumulation of deep-level trap states, it is known that unfavorable non-radiative recombination losses that impede device power outputs exist at the interfaces with bottom contact layers.…”
mentioning
confidence: 99%
“…[31][32][33][34][35] A lack of in-depth understanding of the heterojunction interfaces and appropriate interface designs, specifically the buried interfaces under polycrystalline perovskite films, is impeding further advancements in perovskite photovoltaic performance and stability. [36][37][38][39][40][41][42] To date, many researches mainly focus on the top surfaces of perovskite. [43][44][45][46][47] However, due to the accumulation of deep-level trap states, it is known that unfavorable non-radiative recombination losses that impede device power outputs exist at the interfaces with bottom contact layers.…”
mentioning
confidence: 99%
“…Toluene can form a complex with I 2 , with an absorption band at 500 nm (Figure 5h). [ 51 ] A faster release of I 2 from the pristine film can be observed as compared to the target film. These results showed that incorporation of S2 substantially reduced the ion migration and suppressed I 2 formation.…”
Section: Resultsmentioning
confidence: 99%
“…These include xenon arc, [46,47] metal halide, [48] sulfur plasma, [49] tungsten halogen, and combinations of LED lamps. [25,50,51] Among them, only xenon arc and metal halide emit a significant amount of UV irradiation and their emission spectrum can be tuned to match the actual daylight spectral distribution. Based on our survey of the reported long-term stability profiles, most studies using TiO 2 or SnO 2 as ETLs used white LEDs to monitor device stability.…”
Section: Using White Led Lampsmentioning
confidence: 99%